Abonamiento con dosis de gallinaza y su influencia en las características agronómicas y rendimiento de Capsicum baccatum L. “ají amarillo”, en Zungarococha, distrito de San Juan Bautista-Loreto. 2021 - Yuyarima Iriarte, Juan Felix (2022)
The thesis "Fertilization with doses of chicken and its influence on the agronomic characteristics and yield of Capsicum baccatum L. "ají amarillo", in Zungarococha, District of San Juan Bautista-Loreto. 2021", was held at the Workshop on Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 2.5 of the road to Zungarococha, south of the city of Iquitos, whose coordinates in UTM are: 9576237 North and 682157 South. The type of research was experimental, prospective with one independent variable (Chicken dose) and eight dependent variables (Plant height, Plant diameter, Fruit length, Fruit diameter, Fruit weight, Fruit/plant number, Fruit/plant weight and Fruit/ha weight). The main objective of the research work was to determine if fertilization with chicken doses influences the agronomic characteristics and yield of Capsicum baccatum L. "yellow pepper", in Zungarococha, District of San Juan Bautista-Loreto. 2021. The Statistical Design that was handled was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 2 rows, 5 plants/row and the sampling unit consisted of four plants/experimental unit. With the results obtained at the end of the experiment, the following conclusions were reached: Fertilization with chicken doses influences the agronomic characteristics and yield of Capsicum baccatum L. "yellow pepper"; where the T3 Treatment (50 t of chicken /ha), presented the highest average values of length, diameter, number of fruits, weight of fruit and weight of fruits / ha; the T3 Treatment (50 t of chicken/ha), obtained the best yield of fruit weight/ha with 18.28 t and the best profitability with S/.98,504.00